The Yaoi phenomenon in Thailand and fan/industry interaction - Prasannam, Natthanai (2019)
Access online through this link: https://www.plarideljournal.org/article/the-yaoi-phenomenon-in-thailand-and-fan-industry-interaction
Keywords: Popular culture -- Thailand; Fans (Persons); Gay couples